Money Supply and Inflation in Indonesia: An Analysis of al-Maqrizi's Thought - Widianita, Rika; Hidayat, Faisal; Hidayatullah, Abdul Karim (Universitas Siliwangi, 2024)
Introduction to The Problem: Al-Maqrizi is a Muslim economist who is known for his work on money and inflation. al-Maqrizi argued that the circulation and creation of excessive money by the government will lead to an increase in the prices of goods and services (inflation).Purpose/Objective Study: this study tries to analyze empirically the relationship or influence of the money supply in Indonesia on the Inflation that occurs. It aims to see the government's policy in regulating the amount of money in circulation whether it is in accordance with the needs of the community or not, or even the creation and circulation of money causes inflation.Design/Methodology/Approach: This research is a quantitative study using a descriptive statistical approach to data processing. The data used is secondary data, namely data in the form of money supply and inflation that occurred in Indonesia during the last 32 years (1992 - 2023), the data collection technique used is documentation by collecting data from statistical reports from Bank Indonesia and the Central Bureau of Statistics of Indonesia, as well as books and journals relevant to the research conducted. Data analysis techniques used are correlation and regression.Findings: From the results of data processing, it is concluded that the circulation of money has no effect on inflation in Indonesia. When viewed from the theory put forward by Al-Maqrizi, it can be concluded that the creation or circulation of money circulation that occurred in Indonesia in the last 32 years did not cause inflation, this can be interpreted that the circulation of money in Indonesia by the government is in accordance with the needs of transactions or economic activities in Indonesia, so as not to cause inflation.